Role of cellular senescence in inflammation and regeneration - Yuki Saito; Sena Yamamoto; Takako S. Chikenji (BMC, 2024)
Abstract Cellular senescence is the state in which cells undergo irreversible cell cycle arrest and acquire diverse phenotypes. It has been linked to chronic inflammation and fibrosis in various organs as well as to individual aging. Therefore, eliminating senescent cells has emerged as a potential target for extending healthy lifespans. Cellular senescence plays a beneficial role in many biological processes, including embryonic development, wound healing, and tissue regeneration, which is mediated by the activation of stem cells. Therefore, a comprehensive understanding of cellular senescence, including both its beneficial and detrimental effects, is critical for developing safe and effective treatment strategies to target senescent cells. This review provides an overview of the biological and pathological roles of cellular senescence, with a particular focus on its beneficial or detrimental functions among its various roles.